Cardiac manifestations in a Chinese cohort of fetuses from mothers with anti-Ro and anti-La antibodies - Wang, Xin; Liu, Xiao-wei; Han, Ling; Li, Meng-tao; Zhao, Jiu-liang; Sun, Lin; Han, Jian-cheng; Zeng, Xiao-feng; Tian, Xin-ping; Zhao, Ying; He, Yi-hua (Frontiers in Pediatrics, 2022)
Objectives To analyze the clinical characteristics, echocardiographic features, and prognosis of fetuses based on three groups of cardiac manifestations associated with maternal anti-Ro and anti-La antibodies in China. This study included three groups: the isolated-arrhythmia, isolated-endocardial fibroelastosis (EFE), and mixed groups. Methods We prospectively evaluated 36 fetuses with cardiac manifestations due to maternal anti-Ro and anti-La antibodies from our center between 2016 and 2020 in China. Clinical and echocardiographic data were collected. Results There were 13 patients (36%) in the isolated-arrhythmia group, eight (22%) in the isolated-EFE group, and 15 (42%) in the mixed group. All patients in the isolated-EFE group presented with mild EFE. Severe EFE was identified in four patients (27%) in the mixed group. Atrioventricular block (AVB) was more common in the isolated-arrhythmia group (13, 100%) than in the mixed group (6, 40%; p=0.001). Moderate-severe mitral regurgitation (p=0.006), dilated cardiomyopathy (DCM, p=0.017), and low cardiovascular profile scores (p=0.013) were more common in the mixed group than in the other two groups. Twenty-one mothers decided to terminate the pregnancy and 15 fetuses were born with regular perinatal treatment. They all survived at 1 year of age. One patient in the isolated-arrhythmia group and two in the mixed group required a pacemaker due to third-degree AVB or atrioventricular junctional rhythm. Five patients in the isolated-EFE group and five in the mixed group had no DCM or heart failure and the location of mild EFE was significantly reduced. Conclusion Fetal cardiac manifestations due to maternal anti-Ro and anti-La antibodies can be divided into three groups, i.e., the isolated-arrhythmia, isolated-EFE, and mixed groups. AVB usually occurs in the isolated-arrhythmia group. Severe EFE, moderate-severe mitral regurgitation, and DCM mainly appear in the mixed group. Location of mild EFE significantly reduces after birth and the outcome of fetuses with mild EFE depends on the presence of arrhythmia and its subtypes. Key words: endocardial fibroelastosis, anti-Ro antibodies, atrioventricular block, prenatal diagnosis, echocardiography